Participatory model development of integration of Prasart leprosy colony, Surin Province into general community - อุนรัตน์ โกเมศ; ไกรปุย นิยม; ถุนาพรรณ โฉมศรี; แก่นดี เอกพล (Disease Control Journal, 2013)
This study is the Participation Action Research (PAR) with the main objective to develop participatory model of integration of Prasart leprosy colony, Surin Province into general community under close participation of people effected by leprosy and other relating organization. Research methods included several participatory techniques such as observation, Focus group discussion, narration technique, lesson learned from knowledge management, and future search conference as a process for building effective participation and integration. Population and area studied which being selected under purposive sampling were people affected by Leprosy of Prasart leprosy colony and other related organizations. The study has been conducted for 3 years from October 2009-September 2012. Data collection and analysis were made and presented in terms of qualitative basis under three main processes of integration including preparation, implementation, monitoring and evaluation. Authors also dis¬cussed relating key successful factors involved in the successful integration of Prasart leprosy colony into general community together with relevant recommendation to be useful for further application of sustainable integration of remaining leprosy colonies into normal community.